Uwarunkowania implementacji procesów do organizacji - Grajewski, Piotr (Terms of Processes to Organization Implanting, 2009)
The article at first describes forms of viewing the process approach in different organizations. Next, it shows factors influencing the range of changes orientated on the processes. The article also presents causes of the failure in the process of implanting processing solutions. Moreover, it shows chosen elements of process organization maturity level (level of understanding the idea of process approach, processes management, the strategy of implanting all components of the organization that are orientated on the processes). Finally, it shows the necessity of widen diffusion as an idea increasing necessary flexibility of organization reactions to changeable and dynamic surroundings conduct. Reflections and conclusions included in the article are based on own practical and literary experiences.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 381-388